Evaluation of the Main Potentially Toxic Elements and Bioindicator Organisms - Sarabia, Débora Tavares; Mascarenhas, Maria do Socorro; Batistote, Margareth (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Environmental quality is a recurring concern in the area of public health, as the presence of contaminants can cause changes in the environment and affect human life. Therefore, this study aimed to carry out a bibliographical survey of an exploratory/descriptive nature, through the Science Direct platform, carrying out a screening in order to highlight the main, potentially toxic compounds (EPTs) and bioindicator organisms used in cytotoxicity and genotoxicity analyses. , developed through a review using the following keywords “Potentially Toxic Elements, Toxicity, Genotoxicity, Water Bodies, Aquatic Ecosystem” with a time frame between 2013 and 2023. Some inclusion and exclusion criteria were applied for the selection of articles. Based on the panorama of publications analyzed, around 82% are restricted access and only 18% are open access and there was also a gradual and significant increase in the number of articles published, in the period from 2013 to 2023. During the screening, they were identified several toxic compounds, including heavy metals; medicines; anticorrosives; particulate materials; dyes and microplastics. When evaluating the diversity of organisms used as bioindicators, it is possible to observe the use of fish 36.6%, followed by 8.4% of mussels and only 7% of microorganisms, followed by plants and humans 5.6% respectively. The results of this study highlight the wide diversity of bioindicators and the worrying presence of Potentially Toxic Elements (PTEs) in the environment, which highlights the importance of studies aimed at these compounds. The main organisms used as bioindicators were fish, mussels and microorganisms, plants and human beings. The use of living organisms as bioindicators has potential for environmental management and monitoring due to their versatility in detecting Potentially Toxic Elements, proving to be a valuable green tool to be used in toxicological studies.